A hard carbon material and preparation method thereof, negative electrode sheet and battery
By preoxidizing the plastic precursor and cross-linking with 2,6 pyridine dicarboxylic acid, a stable hard carbon material is formed, which solves the problem of unstable performance of biomass hard carbon material, and achieves high sodium storage capacity and excellent magnification and cyclicity.
Patent Information
- Application Number
- CN202411773769.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-12-05
AI Technical Summary
During the preparation process, biomass hard carbon materials have problems such as unstable performance, low first-time Coulomb efficiency and poor rate performance, and their production is affected by region and seasons.
By preoxidizing the plastic precursor, cross-linking reaction with the preoxidized plastic using 2,6 pyridine dicarboxylic acid as an N-containing dopant to form a three-dimensional network structure, and a structurally stable hard carbon material is obtained through high temperature carbonization.
It improves the sodium storage capacity, rate performance and cycle stability of hard carbon materials, enhances the conductivity and active sites of the materials, and is suitable for large-scale production.
Smart Images

Figure CN119240664B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a hard carbon material and a preparation method thereof, a negative electrode sheet and a battery. Background Art
[0002] Sodium and lithium belong to the same main group and have similar physical and chemical properties. Sodium resources are abundant and low in cost, making sodium-ion batteries a very promising energy storage system. Since the ionic radius of sodium is 30% larger than that of lithium ions, conventional graphite does not have much advantage as a negative electrode material for sodium-ion batteries. Compared with graphite, hard carbon has a larger interlayer spacing and disordered structure, and has a higher reversible specific capacity, and has also been widely used in sodium-ion battery research.
[0003] Hard carbon negative electrode materials are mostly made by pyrolysis of biomass carbon precursors, which is the direction that most negative electrode manufacturers are currently planning. At the same time, biomass raw materials are widely available, and most of them are by-products or waste materials in agricultural production processes. However, the preparation of biomass hard carbon is constrained by regional and seasonal differences, which leads to unstable performance of the prepared hard carbon materials, and there are still problems such as low first coulomb efficiency and poor rate performance. In addition, polymer resin materials are often used to prepare hard carbon negative electrodes, and in addition to commonly used thermosetting resins and thermoplastic resins, there are also many polyester resins (i.e., daily plastics) in life.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a hard carbon material and a preparation method thereof, a negative electrode sheet and a battery. The hard carbon material prepared by the preparation process of the hard carbon material provided by the present invention has a stable structure and exhibits good sodium storage capacity and excellent rate and cyclability.
[0006] The present invention solves the above technical problems through the following technical solutions:
[0007] A first aspect of the present invention provides a method for preparing a hard carbon material, comprising the following steps:
[0008] S1: pre-oxidizing the plastic precursor to obtain a pre-oxidized plastic;
[0009] S2: adding the pre-oxidized plastic obtained in step S1 into a mixed solution of deionized water and alcohol, and then adding 2,6-pyridinedicarboxylic acid to perform a cross-linking reaction to obtain a plastic-based resin carbon precursor;
[0010] S3: Carbonizing the plastic-based resin carbon precursor obtained in step S2 at high temperature to obtain the hard carbon material.
[0011] Preferably, in step S1, the plastic precursor is selected from one or more of polyethylene terephthalate, acrylonitrile-butadiene-styrene copolymer, polyethylene, polyvinyl chloride, and polypropylene;
[0012] Preferably, the plastic precursor is waste plastic.
[0013] Preferably, when the plastic precursor is waste plastic, step S1 is: using a strong oxidant to dissolve and clean the plastic precursor, heat treat, centrifuge and wash, and calcine to obtain a pre-oxidized plastic, and the strong oxidant is selected from one or more of hydrogen peroxide, sodium percarbonate, concentrated sulfuric acid, concentrated nitric acid, and sodium hydroxide.
[0014] Preferably, in step S1, the heat treatment is a constant temperature heat treatment, the heating method of the heat treatment is selected from one or more of water bath heating, oil bath heating, and microwave heating, the temperature of the heat treatment is 50-100° C., and the time of the heat treatment is 1-5 hours;
[0015] Preferably, the calcination temperature is 100-300° C., and the calcination time is 5-15 hours.
[0016] Preferably, the step S2 is: adding the pre-oxidized plastic obtained in step S1 to a mixed solution of deionized water and alcohol, and then adding p-hydroxybenzoic acid and 2,6-pyridinedicarboxylic acid to obtain a plastic-based resin carbon precursor through a cross-linking reaction.
[0017] Preferably, in step S2, the alcohol is selected from one or more of methanol, ethanol, ethylene glycol, and isopropanol, and the volume ratio of the alcohol to deionized water is 1:(1-5).
[0018] Preferably, in step S2, after the pre-oxidized plastic is added to a mixed solution of deionized water and alcohol, the concentration of the pre-oxidized plastic in the mixed solution is 0.1-1.5 g / ml;
[0019] Preferably, in step S2, the mass ratio of the 2,6-pyridinedicarboxylic acid, p-hydroxybenzoic acid and the pre-oxidized plastic is 1:1:(10-120).
[0020] Preferably, in step S2, the cross-linking reaction is carried out by heating in a closed environment, and after the cross-linking reaction, centrifugal filtration, washing and drying steps are also included;
[0021] Preferably, in step S3, the high-temperature carbonization is carried out in one or more atmospheres of nitrogen, argon, helium, and neon; the heating rate of the high-temperature carbonization is 0.5~5°C / min; the temperature of the high-temperature carbonization is 800~1400°C; and the time of the high-temperature carbonization is 3~7 hours.
[0022] A second aspect of the present invention provides a negative electrode plate, the negative electrode plate comprising a hard carbon material, and the hard carbon material is prepared according to the preparation method of the hard carbon material provided by the first aspect of the present invention.
[0023] A third aspect of the present invention provides a battery, comprising the negative electrode plate provided by the second aspect of the present invention.
[0024] Compared with the prior art, this application has the following beneficial effects:
[0025] The preparation method of the hard carbon material provided in the present application first pre-oxidizes the plastic precursor to significantly increase its oxygen-containing functional groups; then uses 2,6-pyridinedicarboxylic acid as a N-containing dopant to form a three-dimensional network structure through a cross-linking reaction with the obtained pre-oxidized plastic, and utilizes the carboxyl functional group of 2,6-pyridinedicarboxylic acid and the hydroxyl functional group of the pre-oxidized plastic to undergo a condensation reaction, and connects the two into a structurally stable layered network macromolecule (i.e., a plastic-based resin carbon precursor) through chemical bonds; at the same time, p-hydroxymethylbenzoic acid is used as a connector to link the pre-oxidized plastic and 2,6-pyridinedicarboxylic acid, the carboxyl groups on it undergo a neutralization reaction with the oxygen-containing functional groups in the plastic, and the hydroxymethyl groups undergo a dehydration condensation reaction with the carboxyl groups in 2,6-pyridinedicarboxylic acid, which can not only introduce the N element in 2,6-pyridinedicarboxylic acid in situ, but also the rigid structure of the benzene ring in its molecule can expand the interlayer spacing of the material. The structure of the hard carbon material obtained after high-temperature carbonization of the plastic-based resin carbon precursor is more stable than that of the hard carbon material prepared by conventional methods in the prior art. The battery using the hard carbon material as the negative electrode active material has better cycle stability and excellent electrochemical performance.
[0026] In the process of preparing hard carbon materials, the present application uses 2,6-pyridinedicarboxylic acid as a N-containing dopant and p-hydroxymethylbenzoic acid as a linker. That is, the degree of polymerization between 2,6-pyridinedicarboxylic acid and pre-oxidized plastic can be enhanced by the linking effect of 2,6-pyridinedicarboxylic acid itself, and the role of p-hydroxybenzoic acid in linking the pre-oxidized plastic and 2,6-pyridinedicarboxylic acid can be used to make the final hard carbon material more stable. The increase in the degree of polymerization of the plastic-based resin carbon precursor will also improve the cycle stability of the hard carbon material after carbonization. Moreover, in the subsequent carbonization, the presence of N element will also inhibit the directional growth of the carbon layer, form pyridine N defects around C, enhance the disorder of the hard carbon material, and expand the interlayer spacing, which is beneficial to increase the conductivity and active sites of the hard carbon material, so that the sodium ion battery equipped with the hard carbon material prepared by the method has excellent electrochemical properties, showing high sodium storage capacity and excellent rate and cycle stability.
[0027] The preparation method of the hard carbon material provided in the present application is simple, feasible, green and environmentally friendly, and can be applied to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a SEM image of the N-containing plastic-based hard carbon (NHC) prepared in Example 2 of the present invention.
[0029] Figure 2 XRD spectra of the N-containing plastic-based hard carbon (NHC) prepared in Example 2 of the present invention and the plastic-based hard carbon (HC) prepared in Comparative Example 1.
[0030] Figure 3 It is a line graph comparing the charging capacities of the N-containing plastic-based hard carbon (NHC) prepared in Example 2 of the present invention and the plastic-based hard carbon (HC) prepared in Comparative Example 1 during the cycle at a rate of 0.1C / 0.1C. DETAILED DESCRIPTION
[0031] In order to make the technical scheme and beneficial effects of the present invention more obvious and easy to understand, the following is a detailed description by listing specific embodiments. Wherein, the drawings are not necessarily drawn to scale, and local features can be enlarged or reduced to more clearly show the details of local features. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually based on conventional experimental conditions. Reagents and raw materials used in the present invention are commercially available unless otherwise specified.
[0032] In the following description, a large number of specific details are given to provide a more thorough understanding of the present application. However, it is obvious to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features known in the art are not described; that is, all features of the actual embodiments are not described here, and well-known functions and steps are not described in detail.
[0033] The purpose of the terms used herein is only to describe specific embodiments and is not intended to be limiting of the present application. When used herein, the singular forms "one", "an" and "said / the" are also intended to include plural forms, unless the context clearly indicates otherwise. It should also be understood that the terms "consisting of" and / or "comprising", when used in this specification, determine the presence of the features, integers, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or groups. When used herein, the term "and / or" includes any and all combinations of the relevant listed items.
[0034] In order to thoroughly understand the present application, detailed steps and detailed structures will be presented in the following description to illustrate the technical solution of the present application. The preferred embodiments of the present application are described in detail below, but in addition to these detailed descriptions, the present application may also have other implementation methods.
[0035] Unless otherwise defined, technical and scientific terms used in this application have the same meanings as those in the technical field to which this application belongs.
[0036] If no specific techniques or conditions are specified in the following examples, the conventional techniques or conditions described in the literature in the art, or the conditions recommended by the product instructions and the manufacturer are generally used. The numerical ranges in the following examples all include the endpoint values.
[0037] [Method for preparing hard carbon material]
[0038] A first aspect of the present invention provides a method for preparing a hard carbon material, which comprises the following steps:
[0039] S1: pre-oxidizing the plastic precursor to obtain a pre-oxidized plastic;
[0040] S2: adding the pre-oxidized plastic obtained in step S1 into a mixed solution of deionized water and alcohol, and then adding 2,6-pyridinedicarboxylic acid to perform a cross-linking reaction to obtain a plastic-based resin carbon precursor;
[0041] S3: Carbonizing the plastic-based resin carbon precursor obtained in step S2 at high temperature to obtain the hard carbon material.
[0042] The preparation method of the hard carbon material provided in the present application first pre-oxidizes the plastic precursor to significantly increase its oxygen-containing functional groups; then uses 2,6-pyridinedicarboxylic acid as a N-containing dopant to form a three-dimensional network structure through a cross-linking reaction with the obtained pre-oxidized plastic, and utilizes the carboxyl functional group of 2,6-pyridinedicarboxylic acid and the hydroxyl functional group of the pre-oxidized plastic to undergo a condensation reaction, and connects the two into a structurally stable layered network macromolecule (i.e., the plastic-based resin carbon precursor) through chemical bonds. In the process of preparing hard carbon materials, the present application uses 2,6-pyridinedicarboxylic acid as a N-containing dopant, and can enhance the degree of polymerization between polymer macromolecules (2,6-pyridinedicarboxylic acid and pre-oxidized plastic) through the linking effect of 2,6-pyridinedicarboxylic acid itself, so that the final hard carbon material is more stable, and the increase in the degree of polymerization of the plastic-based resin carbon precursor will also improve the cycle stability of the hard carbon material after carbonization; and in the subsequent carbonization, due to the presence of N elements, the directional growth of the carbon layer will be inhibited, and pyridine N defects will be formed around C, thereby enhancing the disorder of the hard carbon material and expanding the interlayer spacing, which is beneficial to increase the conductivity and active sites of the hard carbon material, so that the sodium ion battery equipped with the hard carbon material prepared by the method has excellent electrochemical properties, showing high sodium storage capacity and excellent rate and cycle stability.
[0043] In certain embodiments, in step S1, the plastic precursor is selected from one or more of PET (polyethylene terephthalate), ABS resin (acrylonitrile-butadiene-styrene copolymer), PE (polyethylene), PVC (polyvinyl chloride), and PP (polypropylene).
[0044] In certain embodiments, in step S1, the plastic precursor is selected from PET (polyethylene terephthalate).
[0045] In certain embodiments, the plastic precursor is waste plastic.
[0046] In the present application, by using waste plastics as plastic precursors of hard carbon materials, environmental plastic pollution can be effectively reduced, and at the same time, sodium ion batteries equipped with hard carbon materials prepared by this method can be made more green and environmentally friendly.
[0047] In certain embodiments, when the plastic precursor is waste plastic, the step S1 is: using a strong oxidant to dissolve and clean the plastic precursor, heat treat, centrifuge and wash, and calcine to obtain a pre-oxidized plastic.
[0048] Since waste plastics contain a lot of mixed impurities in addition to plastic resins, if the impurities cannot be removed, the subsequent sodium storage capacity of hard carbon materials will be greatly affected, thereby affecting the electrochemical performance of sodium ion batteries equipped with hard carbon materials prepared using this method. In this application, when the plastic precursor is waste plastic, the plastic precursor is pre-oxidized with a strong oxidant, which can effectively remove impurities while introducing a large number of oxygen-containing functional groups, effectively improving the reversible specific capacity, first efficiency, cycle stability and rate performance of sodium ion batteries equipped with hard carbon materials prepared using this method.
[0049] By washing and calcining the plastic precursor after treatment with a strong oxidant, the gas generated by the strong oxidant can be effectively prevented from corroding the pipeline, thereby effectively improving the large-scale production capacity of the preparation method.
[0050] In certain embodiments, in step S1, the strong oxidant is selected from one or more of hydrogen peroxide, sodium percarbonate, concentrated sulfuric acid, concentrated nitric acid, and sodium hydroxide.
[0051] In certain embodiments, in step S1, the strong oxidant is selected from hydrogen peroxide.
[0052] In certain embodiments, in step S1, the heat treatment is a constant temperature heat treatment.
[0053] In certain embodiments, in step S1, the heating method of the heat treatment is selected from one or more of water bath heating, oil bath heating, and microwave heating.
[0054] In some embodiments, in step S1, the temperature of the heat treatment is 50-100°C.
[0055] In certain embodiments, in step S1, the temperature of the heat treatment is 80-100°C, for example, 80°C, 85°C, 90°C, 95°C or 100°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable. Too low a temperature will result in insufficient strong oxidizing effect of hydrogen peroxide, and too high a temperature will result in too fast decomposition of hydrogen peroxide. When the heat treatment temperature is within the above temperature range, the best impurity removal effect can be achieved, effectively improving the reversible specific capacity, first efficiency, cycle stability and rate performance of the sodium ion battery equipped with the hard carbon material prepared by the method.
[0056] In certain embodiments, in step S1, the heat treatment time is 1 to 5 hours.
[0057] In certain embodiments, in step S1, the heat treatment time is 2 to 5 hours, such as 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours, but is not limited to the listed values, and other values not listed in the numerical range are also applicable. In this way, the impurity removal effect of the strong oxidant hydrogen peroxide due to too short a time can be avoided, and the problem that part of the plastic precursor is also dissolved due to too long a time, resulting in a low subsequent plastic yield, can be avoided, and the reversible specific capacity, first efficiency, cycle stability and rate performance of the sodium ion battery equipped with the hard carbon material prepared by the method can be effectively improved.
[0058] In certain embodiments, in step S1, the calcination temperature is 100-300°C.
[0059] In certain embodiments, in step S1, the calcination temperature is 200-300°C, for example, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C or 300°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable. Thus, when the calcination temperature is within the above range, the plastic precursor can be fully oxidized to ensure that the content of oxygen-containing functional groups of the pre-oxidized plastic increases, and the degree of crosslinking with 2,6-pyridinedicarboxylic acid is increased, thereby effectively improving the reversible specific capacity, first efficiency, cycle stability and rate performance of the sodium ion battery equipped with the hard carbon material prepared by the method.
[0060] In certain embodiments, in step S1, the calcination time is 5 to 15 hours.
[0061] In some embodiments, in step S1, the calcination time is 5 to 10 hours, such as 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 9.5 hours or 10 hours, but is not limited to the listed values, and other values not listed in the numerical range are also applicable. Therefore, when the calcination time is within the above range, the plastic can be fully oxidized and partial carbonization caused by excessive calcination time can be prevented, thereby effectively improving the reversible specific capacity, first efficiency, cycle stability and rate performance of the sodium ion battery equipped with the hard carbon material prepared by the method.
[0062] In some embodiments, the step S2 is: adding the pre-oxidized plastic obtained in step S1 to a mixed solution of deionized water and alcohol, and then adding p-hydroxybenzoic acid and 2,6-pyridinedicarboxylic acid to perform a cross-linking reaction to obtain a plastic-based resin carbon precursor.
[0063] In the present application, p-hydroxymethylbenzoic acid is used as a linker to connect the pre-oxidized plastic and 2,6-pyridinedicarboxylic acid. The carboxyl group on it undergoes a neutralization reaction with the oxygen-containing functional group in the plastic, and the hydroxymethyl group undergoes a dehydration condensation reaction with the carboxyl group in 2,6-pyridinedicarboxylic acid, which can not only introduce the N element in 2,6-pyridinedicarboxylic acid in situ, but also the rigid structure of the benzene ring in its molecule can expand the interlayer spacing of the material. In the process of preparing a hard carbon material, the present application uses p-hydroxymethylbenzoic acid as a linker, and the effect of p-hydroxybenzoic acid linking the pre-oxidized plastic and 2,6-pyridinedicarboxylic acid can make the final hard carbon material more stable, thereby making the sodium ion battery equipped with the hard carbon material prepared by the method have excellent electrochemical properties, showing high sodium storage capacity and excellent rate and cycle stability.
[0064] In certain embodiments, in step S2, the alcohol is selected from one or more of methanol, ethanol, ethylene glycol, and isopropanol.
[0065] In certain embodiments, in step S2, the alcohol is selected from ethanol.
[0066] In certain embodiments, in step S2, the volume ratio of the alcohol to deionized water is 1:(1-5).
[0067] In certain embodiments, in step S2, the volume ratio of ethanol to deionized water is 1:(1-5).
[0068] In certain embodiments, in step S2, the volume ratio of the alcohol to deionized water is 1:(3-5), for example, 1:3, 1:3.1, 1:3.2, 1:3.3, 1:3.4, 1:3.5, 1:3.6, 1:3.7, 1:3.8, 1:3.9, 1:4, 1:4.1, 1:4.2, 1:4.3, 1:4.4, 1:4.5, 1:4.6, 1:4.7, 1:4.8, 1:4.9 or 1:5, but is not limited to the listed values, and other values not listed within the numerical range are also applicable. Therefore, when the volume ratio of the alcohol and deionized water is within the above range, it can effectively prevent the generation of excessive gas due to the excessive volume ratio of alcohol, which in turn leads to the pore size of the prepared hard carbon material being too large (which will cause the specific surface area of the material to increase abnormally), and the pore-forming effect being poor due to the low volume ratio of alcohol, which leads to too few pores formed in the material, which is not conducive to the storage and transmission of sodium ions, and ultimately causes the problem of decreased first efficiency of the battery including the hard carbon material, thereby effectively improving the reversible specific capacity, first efficiency, cycle stability and rate performance of the sodium ion battery equipped with the hard carbon material prepared by the method.
[0069] In certain embodiments, in step S2, the volume ratio of ethanol to deionized water is 1:(3-5), for example, 1:3, 1:3.1, 1:3.2, 1:3.3, 1:3.4, 1:3.5, 1:3.6, 1:3.7, 1:3.8, 1:3.9, 1:4, 1:4.1, 1:4.2, 1:4.3, 1:4.4, 1:4.5, 1:4.6, 1:4.7, 1:4.8, 1:4.9 or 1:5, but is not limited to the listed values, and other values not listed within the numerical range are also applicable. Therefore, when the volume ratio of the ethanol and deionized water is within the above range, it can effectively prevent the generation of excessive gas due to the excessive volume proportion of ethanol, which in turn leads to the pore size of the prepared hard carbon material being too large (which will cause the specific surface area of the material to increase abnormally), and the pore-forming effect is poor due to the low volume proportion of ethanol, which leads to too few pores formed in the material, which is not conducive to the storage and transmission of sodium ions, and ultimately causes the problem of decreased first efficiency of the battery including the hard carbon material, thereby effectively improving the reversible specific capacity, first efficiency, cycle stability and rate performance of the sodium ion battery equipped with the hard carbon material prepared by the method.
[0070] In certain embodiments, in step S2, after the pre-oxidized plastic is added to a mixed solution of deionized water and alcohol, the concentration of the pre-oxidized plastic in the mixed solution is 0.1-1.5 g / ml.
[0071] In certain embodiments, in step S2, after the pre-oxidized plastic is added to a mixed solution of deionized water and alcohol, the concentration of the pre-oxidized plastic in the mixed solution is 0.2 to 0.5 g / ml, for example 0.2 g / ml, 0.25 g / ml, 0.3 g / ml, 0.35 g / ml, 0.4 g / ml, 0.45 g / ml or 0.5 g / ml, but not limited to the listed values, and other values not listed within the numerical range are also applicable. Thus, when the concentration of the pre-oxidized plastic in the mixed solution is within the above numerical range, the cross-linking reaction is easier to carry out and the degree of cross-linking between the pre-oxidized plastic and 2,6-pyridinedicarboxylic acid is significantly improved, so that the obtained plastic-based resin carbon precursor is more uniform and the stability of the molecular chain is effectively improved, thereby effectively improving the reversible specific capacity, first efficiency, cycle stability and rate performance of the battery using the hard carbon material.
[0072] In certain embodiments, in step S2, the mass ratio of the 2,6-pyridinedicarboxylic acid to the pre-oxidized plastic is 1:(10-120).
[0073] In certain embodiments, in step S2, the mass ratio of the 2,6-pyridinedicarboxylic acid, p-hydroxybenzoic acid and the pre-oxidized plastic is 1:1:(20~50), such as 1:1:20, 1:1:25, 1:1:30, 1:1:35, 1:1:40, 1:1:45 or 1:1:50, but not limited to the listed values, and other values not listed within the numerical range are also applicable. Thus, when the mass ratio of the 2,6-pyridinedicarboxylic acid to the pre-oxidized plastic is within the above-mentioned resin range, the content of N element doped in the hard carbon material can be increased, which is beneficial to the increase of interlayer spacing, conductivity and N active sites; it can also avoid the problem of too many defects caused by the introduction of more N elements due to the high content of 2,6-pyridinedicarboxylic acid, thereby effectively improving the reversible specific capacity, first efficiency, cycle stability and rate performance of the sodium ion battery equipped with the hard carbon material prepared by the method.
[0074] In certain embodiments, in step S2, the reaction condition is a heating reaction in a closed environment.
[0075] In certain embodiments, in step S2, the heating method is heating in a hydrothermal reactor.
[0076] In certain embodiments, in step S2, the heating temperature is 100-150°C.
[0077] In some embodiments, in step S2, the heating temperature is 120-150°C, such as 120°C, 130°C, 140°C or 150°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable. Thus, when the temperature of the hydrothermal heating is within the above range, the movement between the polymer chains of 2,6-pyridinedicarboxylic acid and the pre-oxidized plastic can be enhanced without destroying the network macromolecular structure, thereby making the polymer chains of the obtained plastic-based resin carbon precursor more closely cross-linked, thereby effectively improving the reversible specific capacity, first efficiency, cycle stability and rate performance of the sodium ion battery equipped with the hard carbon material prepared by the method.
[0078] In certain embodiments, in step S2, the heating time is 3 to 7 hours.
[0079] In certain embodiments, in step S2, the heating time is 3 to 5 hours, for example, 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0080] In certain embodiments, in step S2, after the reaction, the steps of centrifugal filtration, washing and drying are also included.
[0081] In certain embodiments, the cleaning completion standard is that the pH of the mixed solution is 7.
[0082] In certain embodiments, in step S3, the high temperature carbonization is performed under one or more atmospheres of nitrogen, argon, helium, and neon.
[0083] In certain embodiments, in step S3, the high temperature carbonization is performed under a nitrogen atmosphere.
[0084] In certain embodiments, in step S3, the heating rate of the high temperature carbonization is 0.5-5°C / min.
[0085] In certain embodiments, in step S3, the heating rate of the high temperature carbonization is 0.5-4°C / min, such as 0.5°C / min, 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min, 3°C / min, 3.5°C / min or 4°C / min, but is not limited to the listed values, and other values not listed within the numerical range are also applicable. Thus, when the heating rate is within the above range, it can effectively prevent the increase in the planar imperfection and the number of defects during the growth of the carbon layer caused by the increase in the pyrolysis rate of the plastic-based resin carbon precursor, which in turn leads to the problem of an increase in the irreversible capacity of the first charge and discharge cycle of the sodium ion battery equipped with the hard carbon material prepared by the method.
[0086] In some embodiments, in step S3, the high temperature carbonization temperature is 800-1400°C.
[0087] In some embodiments, in step S3, the temperature of the high temperature carbonization is 1200-1300°C, such as 1200°C, 1210°C, 1220°C, 1230°C, 1240°C, 1250°C, 1260°C, 1270°C, 1280°C, 1290°C or 1300°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable. In this way, it is possible to prevent the carbonization temperature from being too low, which is not conducive to the rearrangement of carbon and the reconstruction of a partially closed-cell structure, thereby avoiding the problem of an increase in the irreversible capacity of a sodium ion battery equipped with a hard carbon material prepared by the method in the first charge and discharge cycle.
[0088] In certain embodiments, in step S3, the high temperature carbonization time is 3 to 7 hours.
[0089] In certain embodiments, in step S3, the high temperature carbonization time is 3 to 5 hours, for example, 3 hours, 3.5 hours, 4 hours, 4.5 hours or 5 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0090] [Negative electrode]
[0091] The second aspect of the present invention provides a negative electrode plate, which includes a negative electrode active material, a conductive agent and a binder, wherein the negative electrode active material is a hard carbon material prepared according to the preparation method of the hard carbon material provided by the first aspect of the present invention.
[0092] The present application does not particularly limit the types of the conductive agent and the binder in the negative electrode plate, as long as the purpose of the present application can be achieved. For example, the binder may include but is not limited to polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylic (ester) styrene butadiene rubber, epoxy resin or nylon, etc. For example, the conductive agent may include but is not limited to: conductive carbon black, acetylene black, Ketjen black, carbon fiber or any combination thereof.
[0093] The present application has no particular restriction on the mass ratio of the negative electrode active material, the conductive agent and the binder in the negative electrode sheet, and those skilled in the art can select it according to actual needs as long as the purpose of the present application can be achieved.
[0094] The present application has no particular restrictions on the preparation method of the negative electrode sheet, and any preparation method known in the art may be selected as long as the purpose of the present application can be achieved.
[0095] It should be understood that since the negative electrode plate provided in the present application includes the hard carbon material prepared by the preparation method of the hard carbon material provided in the first aspect of the present invention, the beneficial effects of preparing the hard carbon material described in any of the above embodiments are applicable to the negative electrode plate.
[0096] [Battery]
[0097] A third aspect of the present invention provides a battery, comprising the negative electrode plate provided by the second aspect of the present invention.
[0098] It should be understood that, since the battery provided in the present application includes the negative electrode plate described in the second aspect of the present invention, the beneficial effects of preparing the hard carbon material described in any of the above embodiments are applicable to the battery.
[0099] In some embodiments, the battery further comprises a positive electrode sheet, an electrolyte and a separator. Typically, a battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, and the separator is disposed between the positive electrode sheet and the negative electrode sheet. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is disposed between the positive electrode sheet and the negative electrode sheet, and mainly plays the role of preventing the positive / negative electrode from short-circuiting, while allowing ions to pass through.
[0100] In some embodiments, the battery may be a secondary battery or a primary battery, preferably a secondary battery. For example, the battery may be a sodium ion battery, etc., but is not limited thereto. The battery structure of the present application includes but is not limited to a soft-pack sodium ion battery, a square hard-shell battery, or a cylindrical hard-shell battery, etc.
[0101] The battery of the present application also includes a packaging shell for accommodating a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the art in a sodium ion battery, and the present application does not limit the above other components. The present application does not specifically limit the packaging shell, and it can be a packaging shell known in the art, as long as it can achieve the purpose of the present application.
[0102] The present invention has no special restrictions on the preparation method of the battery, and the technical scheme for preparing a hard carbon material into a battery such as a secondary battery, which is well known to those skilled in the art, can be adopted.
[0103] The method of the present invention is described below by means of specific examples. It should be understood that these examples are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following examples; the implementation conditions adopted in the examples can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in routine experiments. Example 1
[0104] This embodiment provides a method for preparing N-containing plastic-based hard carbon, and the specific preparation steps are as follows:
[0105] (1) Take 50g of waste plastic (PET) as a precursor, measure 100ml of 10% H2O2 strong oxidant for dissolution and cleaning, heat treat at 80℃ for 2h, and centrifuge to obtain plastic (PET) with impurities removed;
[0106] (2) The cleaned plastic obtained in the above step is calcined in a muffle furnace at 200° C. under air atmosphere for 10 h to obtain a pre-oxidized plastic (OPET);
[0107] (3) Add 2 g of 2,6-pyridinedicarboxylic acid to a mixture of 40 g of OPET powder, 40 ml of ethanol and 160 ml of deionized water, heat in a closed hydrothermal reactor at 120 °C for 5 h to allow a cross-linking reaction to occur, centrifuge and filter, wash to pH = 7, and dry to obtain a plastic-based resin carbon precursor;
[0108] (4) The carbon precursor obtained above was heated to 1200°C at 2°C / min in a N2 atmosphere and carbonized for 5 h to obtain N-containing plastic-based hard carbon (NHC). Example 2
[0109] This embodiment provides a method for preparing N-containing plastic-based hard carbon, and the specific preparation steps are as follows:
[0110] (1) Take 50g of waste plastic (PET) as a precursor, measure 100ml of 10% H2O2 strong oxidant for dissolution and cleaning, heat treat at 80℃ for 2h, and centrifuge to obtain plastic (PET) with impurities removed;
[0111] (2) The cleaned plastic obtained in the above step is calcined in a muffle furnace at 200° C. under air atmosphere for 10 h to obtain a pre-oxidized plastic (OPET);
[0112] (3) A mixture of 40 g of OPET powder, 40 ml of ethanol and 160 ml of deionized water was added with 2 g of p-hydroxybenzoic acid and 2 g of 2,6-pyridinedicarboxylic acid, heated in a closed environment at 120 ° C hydrothermal reactor for 5 h to cause a cross-linking reaction, centrifuged and filtered, washed to pH = 7, and dried to obtain a plastic-based resin carbon precursor;
[0113] (4) The carbon precursor obtained above was heated to 1200°C at 2°C / min in a N2 atmosphere and carbonized for 5 h to obtain N-containing plastic-based hard carbon (NHC). Example 3
[0114] This embodiment provides a method for preparing N-containing plastic-based hard carbon, and the specific preparation steps are as follows:
[0115] (1) Take 50g of waste plastic (PET) as a precursor, measure 100ml of 10% H2O2 strong oxidant for dissolution and cleaning, heat treat at 80℃ for 2h, and centrifuge to obtain plastic (PET) with impurities removed;
[0116] (2) The cleaned plastic obtained in the above step is calcined in a muffle furnace at 100° C. under air atmosphere for 10 h to obtain a pre-oxidized plastic (OPET);
[0117] (3) A mixture of 40 g of OPET powder, 40 ml of ethanol and 160 ml of deionized water was added with 2 g of p-hydroxybenzoic acid and 2 g of 2,6-pyridinedicarboxylic acid, heated in a closed environment at 120 ° C hydrothermal reactor for 5 h to cause a cross-linking reaction, centrifuged and filtered, washed to pH = 7, and dried to obtain a plastic-based resin carbon precursor;
[0118] (4) The carbon precursor obtained above was heated to 1200°C at 2°C / min in a N2 atmosphere and carbonized for 5 h to obtain N-containing plastic-based hard carbon (NHC). Example 4
[0119] This embodiment provides a method for preparing N-containing plastic-based hard carbon, and the specific preparation steps are as follows:
[0120] (1) Take 50g of waste plastic (PET) as a precursor, measure 100ml of 10% H2O2 strong oxidant for dissolution and cleaning, heat treat at 80℃ for 2h, and centrifuge to obtain plastic (PET) with impurities removed;
[0121] (2) The cleaned plastic obtained in the above step is calcined in a muffle furnace at 100° C. under air atmosphere for 10 h to obtain a pre-oxidized plastic (OPET);
[0122] (3) A mixture of 50 g of OPET powder, 10 ml of ethanol and 40 ml of deionized water was added with 2.5 g of p-hydroxybenzoic acid and 2.5 g of 2,6-pyridinedicarboxylic acid, heated in a closed environment at 120 ° C in a hydrothermal reactor for 5 h to cause a cross-linking reaction, centrifuged and filtered, washed to pH = 7, and dried to obtain a plastic-based resin carbon precursor;
[0123] (4) The carbon precursor obtained above was heated to 1200°C at 2°C / min in a N2 atmosphere and carbonized for 5 h to obtain N-containing plastic-based hard carbon (NHC). Example 5
[0124] This embodiment provides a method for preparing N-containing plastic-based hard carbon, and the specific preparation steps are as follows:
[0125] (1) Take 50g of waste plastic (PET) as a precursor, measure 100ml of 10% H2O2 strong oxidant for dissolution and cleaning, heat treat at 80℃ for 2h, and centrifuge to obtain plastic (PET) with impurities removed;
[0126] (2) The cleaned plastic obtained in the above step is calcined in a muffle furnace at 100° C. under air atmosphere for 10 h to obtain a pre-oxidized plastic (OPET);
[0127] (3) A mixture of 40 g of OPET powder, 40 ml of ethanol and 160 ml of deionized water was added with 0.4 g of p-hydroxybenzoic acid and 0.4 g of 2,6-pyridinedicarboxylic acid, heated in a closed hydrothermal reactor at 120 °C for 5 h to allow a cross-linking reaction to occur, centrifuged and filtered, washed to a pH of 7, and dried to obtain a plastic-based resin carbon precursor;
[0128] (4) The carbon precursor obtained above was heated to 1200°C at 2°C / min in a N2 atmosphere and carbonized for 5 h to obtain N-containing plastic-based hard carbon (NHC). Example 6
[0129] This embodiment provides a method for preparing N-containing plastic-based hard carbon, and the specific preparation steps are as follows:
[0130] (1) Take 50g of waste plastic (PET) as a precursor, measure 100ml of 10% H2O2 strong oxidant for dissolution and cleaning, heat treat at 80℃ for 2h, and centrifuge to obtain plastic (PET) with impurities removed;
[0131] (2) The cleaned plastic obtained in the above step is calcined in a muffle furnace at 200° C. under air atmosphere for 10 h to obtain a pre-oxidized plastic (OPET);
[0132] (3) A mixture of 40 g of OPET powder, 100 ml of ethanol and 100 ml of deionized water was added with 2 g of p-hydroxybenzoic acid and 2 g of 2,6-pyridinedicarboxylic acid, heated in a closed environment at 120 ° C hydrothermal reactor for 5 h to cause a cross-linking reaction, centrifuged and filtered, washed to pH = 7, and dried to obtain a plastic-based resin carbon precursor;
[0133] (4) The carbon precursor obtained above was heated to 1200°C at 2°C / min in a N2 atmosphere and carbonized for 5 h to obtain N-containing plastic-based hard carbon (NHC). Example 7
[0134] This embodiment provides a method for preparing N-containing plastic-based hard carbon, and the specific preparation steps are as follows:
[0135] (1) Take 50g of waste plastic (PET) as a precursor, measure 100ml of 10% H2O2 strong oxidant for dissolution and cleaning, heat treat at 80℃ for 2h, and centrifuge to obtain plastic (PET) with impurities removed;
[0136] (2) The cleaned plastic obtained in the above step is calcined in a muffle furnace at 200° C. under air atmosphere for 10 h to obtain a pre-oxidized plastic (OPET);
[0137] (3) A mixture of 40 g of OPET powder, 40 ml of ethanol and 160 ml of deionized water was added with 2 g of p-hydroxybenzoic acid and 2 g of 2,6-pyridinedicarboxylic acid, heated in a closed environment at 120 ° C hydrothermal reactor for 5 h to cause a cross-linking reaction, centrifuged and filtered, washed to pH = 7, and dried to obtain a plastic-based resin carbon precursor;
[0138] (4) The carbon precursor obtained above was heated to 1000°C at 5°C / min in a N2 atmosphere and carbonized for 5 h to obtain N-containing plastic-based hard carbon (NHC). Comparative Example 1
[0139] This embodiment provides a method for preparing plastic-based hard carbon, and the specific preparation steps are as follows:
[0140] (1) Take 50g of waste plastic (PET) as a precursor, measure 100ml of 10% H2O2 strong oxidant for dissolution and cleaning, heat treat at 80℃ for 2h, and centrifuge to obtain plastic (PET) with impurities removed;
[0141] (2) The carbon precursor obtained above was heated to 1200°C at 2°C / min in a N2 atmosphere for high temperature carbonization for 5 h to obtain plastic-based hard carbon (HC). Comparative Example 2
[0142] This embodiment provides a method for preparing plastic-based pre-oxidized hard carbon, and the specific preparation steps are as follows:
[0143] (1) Take 50g of waste plastic (PET) as a precursor, measure 100ml of 10% H2O2 strong oxidant for dissolution and cleaning, heat treat at 80℃ for 2h, and centrifuge to obtain plastic (PET) with impurities removed;
[0144] (2) The cleaned plastic obtained in the above step is calcined in a muffle furnace at 200° C. under air atmosphere for 10 h to obtain a pre-oxidized plastic (OPET);
[0145] (3) The carbon precursor obtained above was heated to 1200°C at 2°C / min in a N2 atmosphere and carbonized for 5 h to obtain plastic-based hard carbon (HC). Comparative Example 3
[0146] This embodiment provides a method for preparing N-containing plastic-based hard carbon, and the specific preparation steps are as follows:
[0147] (1) Take 50g of waste plastic (PET) as a precursor, measure 100ml of 10% H2O2 strong oxidant for dissolution and cleaning, heat treat at 80℃ for 2h, and centrifuge to obtain plastic (PET) with impurities removed;
[0148] (2) The cleaned plastic obtained in the above step is calcined in a muffle furnace at 200° C. under air atmosphere for 10 h to obtain a pre-oxidized plastic (OPET);
[0149] (3) A mixture of 40 g of OPET powder, 40 ml of ethanol and 160 ml of deionized water was added with 2 g of urea, heated in a closed environment at 120 ° C hydrothermal reactor for 5 h to cause a cross-linking reaction, centrifuged and filtered, washed to pH = 7, and dried to obtain a plastic-based resin carbon precursor;
[0150] (4) The carbon precursor obtained above was heated to 1200°C at 2°C / min in a N2 atmosphere and carbonized for 5 h to obtain N-containing plastic-based hard carbon (NHC).
[0151] Electrochemical performance test
[0152] The hard carbon materials obtained in Examples 1-7 and Comparative Examples 1-3 were prepared into half-cells for performance testing according to the following method:
[0153] The active material (the hard carbon material in Examples 1 to 7 and Comparative Examples 1 to 3 is used as the active material respectively): conductive carbon black (SP): carboxymethyl cellulose (CMC): styrene butadiene rubber (SBR) = 95:1:1.5:2.5 (mass ratio) is mixed and evenly coated on aluminum foil, and the coated electrode is placed in a vacuum drying oven at 80°C and dried for 12 hours to prepare a negative electrode. The metal sodium sheet is used as the positive electrode, the negative electrode prepared by the above method is used as the negative electrode, and 1 mol NaPF6 (EC / DEC=1:1) + 5% FEC is used as the electrolyte, and a CR2032 button battery is assembled in an argon-protected glove box.
[0154] 1. Test of the first discharge capacity, first charge capacity and first coulomb efficiency: The button cell prepared according to the above method was discharged and charged at 0.05C / 0.1C rate in turn, with a voltage range of 0~2 V. Specifically: discharge at 0.05C rate to 0V, record the discharge capacity at this time as the first discharge capacity; then charge at 0.1C rate to 2V, record the charge capacity at this time as the first charge capacity; first coulomb efficiency = first charge capacity / first discharge capacity × 100%. The test results are shown in Table 1.
[0155] Table 1
[0156]
[0157] As can be seen from Table 1, the button-type half-cells using the N-containing plastic-based hard carbon materials prepared in Examples 1 to 7 as negative electrode active materials all have relatively high first inventory efficiencies, all exceeding 82%; among them, the first inventory efficiency of Example 2 reached 91.3%. The first coulombic efficiency of Comparative Example 1 was 68.1% and the first coulombic efficiency of Comparative Example 3 was 69.2%, which were much lower than the first efficiency of 91.3% in Example 2. This shows that the key to preparing N-containing plastic-based hard carbon is to expand the interlayer spacing and enhance the structural stability through the cross-linking reaction between 2,6-pyridinedicarboxylic acid and the pre-oxidized plastic base, which is beneficial to improving the specific capacity and first efficiency of the sodium ion battery finally prepared; and when p-hydroxybenzoic acid is present, it plays a role in linking the pre-oxidized plastic and 2,6-pyridinedicarboxylic acid to further improve the first efficiency of the battery.
[0158] 2. Capacity retention rate test: The button battery prepared as above is first discharged to 0V with 0.5C constant current, and then charged to 2V with 0.5C constant current. The charging capacity at this time is recorded as the first-cycle charging capacity, which is one cycle. Repeat this process for 100 cycles, and record the charging capacity of the 100th cycle. Capacity retention rate = charging capacity of the 100th cycle / charging capacity of the first cycle × 100%.
[0159] Table 2
[0160]
[0161] As can be seen from Table 2, the button-type half-cells using the N-containing plastic-based hard carbon materials prepared in Examples 1 to 7 as negative electrode active materials all have high capacity retention rates, all exceeding 85%; among them, the capacity retention rate of Example 2 reaches 93.6%. The capacity retention rates of Comparative Examples 1 to 3 are only 71.3%-73.7%, among which Comparative Example 3 is 71.3%, which is much lower than 93.6% in Example 2. This shows that the present application embodiment has an extremely excellent effect by using 2,6-pyridinedicarboxylic acid as a N-containing dopant in the process of preparing hard carbon materials, and the role of p-hydroxybenzoic acid in linking pre-oxidized plastics and 2,6-pyridinedicarboxylic acid makes the C content of the material high and has a carboxyl functional group. On this basis, it also contains pyridine N, so that the pyridine N in the hard carbon material finally obtained is more conducive to becoming a sodium ion storage active site, so that the sodium ion battery of the hard carbon material has excellent electrochemical properties and exhibits excellent capacity retention.
[0162] 3. Cycle performance test: At 25°C, the button battery prepared as above was activated (activation treatment: discharge to 0V with a constant current of 0.05C; then charge to 2V with a constant current of 0.1C, repeat this step 2 times to complete the activation treatment), and then discharge to 0V with a constant current of 0.1C, and then charge to 2V with a constant current of 0.1C, this is one cycle; repeat this process and record the charging capacity of each cycle of the button battery. The charging capacity line graph of the button battery prepared with the hard carbon material as the negative electrode active material in Example 2 (NHC) and Comparative Example 1 (HC) is shown in the figure below: Figure 3 As shown (two parallel sets for each material).
[0163] from Figure 3 It can be seen that the button cell prepared with NHC as the negative electrode active material in Example 2 has significantly better cycle performance at 0.1C / 0.1C rate than the HC in Comparative Example 1. This is because in the process of preparing the hard carbon material in Example 2 of the present application, 2,6-pyridinedicarboxylic acid is used as a N-containing dopant, which increases the degree of polymerization of the plastic-based resin carbon precursor, thereby making the cycle stability of the obtained hard carbon material higher. Figure 3 It can also be seen that the cyclic performance differences between the parallel samples are small, indicating that the preparation method of the NHC material provided in the present application has high reproducibility and can be applied on a large scale.
[0164] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations included in the claims. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.
Claims
1. A method for preparing a hard carbon material, characterized in that: The steps include: S1: pre-oxidizing the plastic precursor to obtain a pre-oxidized plastic; S2: adding the pre-oxidized plastic obtained in step S1 into a mixed solution of deionized water and alcohol, and then adding 2,6-pyridinedicarboxylic acid to perform a cross-linking reaction to obtain a plastic-based resin carbon precursor; S3: Carbonizing the plastic-based resin carbon precursor obtained in step S2 at high temperature to obtain the hard carbon material.
2. The method for preparing a hard carbon material according to claim 1, characterized in that: In step S1, the plastic precursor is selected from one or more of polyethylene terephthalate, acrylonitrile-butadiene-styrene copolymer, polyethylene, polyvinyl chloride, and polypropylene; And / or, the plastic precursor is waste plastic.
3. The method for preparing a hard carbon material according to claim 2, characterized in that: When the plastic precursor is waste plastic, step S1 is: using a strong oxidant to dissolve and clean the plastic precursor, heat treat, centrifuge and wash, and calcine to obtain a pre-oxidized plastic, wherein the strong oxidant is selected from one or more of hydrogen peroxide, sodium percarbonate, concentrated sulfuric acid, and concentrated nitric acid.
4. The method for preparing a hard carbon material according to claim 3, characterized in that: In step S1, the heat treatment is a constant temperature heat treatment, the heating method of the heat treatment is selected from one or more of water bath heating, oil bath heating, and microwave heating, the temperature of the heat treatment is 50-100° C., and the time of the heat treatment is 1-5 hours; And / or, in step S1, the calcination temperature is 100-300° C., and the calcination time is 5-15 hours.
5. The method for preparing a hard carbon material according to claim 1, characterized in that: The step S2 is: adding the pre-oxidized plastic obtained in step S1 to a mixed solution of deionized water and alcohol, and then adding p-hydroxybenzoic acid and 2,6-pyridinedicarboxylic acid to obtain a plastic-based resin carbon precursor through a cross-linking reaction.
6. The method for preparing a hard carbon material according to claim 5, characterized in that: In step S2, the alcohol is selected from one or more of methanol, ethanol, ethylene glycol, and isopropanol, and the volume ratio of the alcohol to deionized water is 1:(1-5).
7. The method for preparing a hard carbon material according to claim 6, characterized in that: In step S2, after the pre-oxidized plastic is added into a mixed solution of deionized water and alcohol, the concentration of the pre-oxidized plastic in the mixed solution is 0.1-1.5 g / ml; And / or, in step S2, the mass ratio of the 2,6-pyridinedicarboxylic acid, p-hydroxybenzoic acid and the pre-oxidized plastic is 1:1:(10~120).
8. The method for preparing a hard carbon material according to any one of claims 1 to 6, characterized in that: In step S2, the cross-linking reaction is carried out under the condition of heating in a closed environment, and after the cross-linking reaction, centrifugal filtration, washing and drying steps are also included; And / or, in step S3, the high-temperature carbonization is carried out in one or more atmospheres of nitrogen, argon, helium, and neon; the heating rate of the high-temperature carbonization is 0.5~5°C / min; the temperature of the high-temperature carbonization is 800~1400°C; and the time of the high-temperature carbonization is 3~7 hours.
9. A negative electrode plate, characterized in that: The negative electrode plate comprises a hard carbon material, and the hard carbon material is prepared according to the method for preparing a hard carbon material according to any one of claims 1-8.
10. A battery, characterized in that: The battery comprises the negative electrode sheet as claimed in claim 9.
Citation Information
Patent Citations
Preparation method for reconstructing functional groups on surface of hard carbon negative electrode
CN118515259A
Hard carbon material with high disorder degree
CN118693275A